COVID-19 Vaccine Hesitancy Among Reproductive-Aged Females [A129]. (May 2022) - Gilani, Sonia; Butler, Leah; Shamshuddin, Nabiha; Class, Quetzal; Ganti, Amitha
Abstract : INTRODUCTION: Initial COVID-19 vaccine trials excluded pregnant individuals, making eventual vaccine recommendations non-generalizable. After noninferiority was established, the Centers for Disease Control and Prevention, World Health Organization, and American College of Obstetricians and Gynecologists supported vaccination of this group. However, only 31% of pregnant patients accepted vaccination. This study aims to assess COVID-19 vaccine hesitancy in reproductive-aged females. METHODS: We developed a REDCap survey using a validated COVID-19 vaccine hesitancy survey tool. From August to November 2021, women aged 18–50 years were recruited from inpatient and outpatient obstetrics and gynecology services at the University of Illinois Hospital. We performed t tests and ANOVA statistics using SPSS. RESULTS: A total of 51 patients partially or fully completed the survey. The results revealed that Black individuals are more hesitant than Hispanic and White individuals ( F 2, 44 =3.45, P <.50). Specifically, Black women differed in the belief that the COVID-19 vaccine is safe overall ( F 2, 44 =5.62, P <0.01) and in pregnancy ( F 2, 46 =4.95, P <0.01). Pregnant patients were less confident that the COVID-19 vaccine is safe overall ( F 2, 45 =7.44, P <0.01) as well as in pregnancy ( F 2, 47 =6.26, P <0.01) compared to those recently pregnant or not pregnant. Individuals who declined the flu vaccine were more likely to be vaccine hesitant ( t 46 =–4.49, P <.001). Participants' age, occupation, and contraception status were not associated with vaccine hesitancy. CONCLUSION: Existing vaccine hesitancy highlights the need to study misconceptions regarding the safety of the COVID-19 vaccine.